. Is society willing to pay for ecosystem services? The case of the caldén forest (Neltuma caldenia Burkart) in central Argentina (Semiárida, 2025)
Forests, as components of terrestrial biological systems, play a critical role in the context of climate change and as providers of ecosystem services. However, does society associated with forests hold a positive valuation of their services? Is society capable of discerning forest intrinsic value in the regulation and preservation of biological systems? The Caldén forest (Neltuma caldenia (Burkart) C.E. Hughes & G.P. Lewis) represents the southernmost woody formation of the Espinal biome in central Argentina. Its current surface area has been drastically reduced to approximately 2,294,000 hectares. Historically, overexploitation and land-use change have led to the degradation of these ecosystems or their transformation into agricultural or livestock areas. To explore public perception regarding the Caldén forest and the non-compulsory willingness to pay for the services it provides, a semi-structured qualitative weighted survey was employed. The results show that there is a greater recognition of regulatory services compared to tangible and cultural goods provided by the forest. Additionally, a strong willingness to pay for ecosystem services was detected, with 64 % of respondents answering affirmatively. Based on these findings, it can be inferred that the community in the proximity of the Caldén forest area recognizes the importance of native forests as providers of ecosystem services, as suggested by their willingness to donate. Nevertheless, there is a concerning signal regarding the lower valuation and awareness among younger age groups. An analysis of forests that includes social valuation provides a comprehensive approach to their significance in the context of global change.
Keywords: Espinal; Biological systems; Neltuma; semi-structured survey